A study of pattern of vitamin D deficiency in newborns with reference to its gestational age and birth weight - Narayan, Raghvendra; Singh, Shivani; Singh, Om Prakash (International Journal of Contemporary Pediatrics, 2020)
Background: Deficiency of Vitamin D is a prominent health problem globally and its severity is significant in countries like India regardless of age, gender, race and geographical distribution. It is presently the most untreated nutritional deficiency worldwide. Vitamin D during pregnancy has an increasingly recognized range of functions such as immune modulation, lung development etc. Hence, having the potential to influence many factors in the developing fetus. Effects of vitamin D deficiency on fetal health is abundant; some being for brief period of time and others may become apparent in later life. Objectives of this study the pattern of vitamin D deficiency in newborns with reference to its gestational age and birth weight. Methods: This was a hospital-based prospective observational study. Total 100 neonates born at MMIMSR, Ambala were enrolled out of which 50 were term and 50 preterm. Results: Out of 100 newborns delivered, 53 newborns were vitamin D deficient. Premature newborns having 32 (60%) and term newborn having 21 (40%) were found to be deficient in vitamin D. Mean 25 (OH) levels were 21.81 ng/dl. Conclusions: More than half newborns were deficient in vitamin D. Premature newborns had relatively low levels as compared to the term newborns and the difference between two were found statistically significant.